EFEKTIVITAS MEDIA PEMELAJARAN PADA ABAD 21 DI NGAWI JAWA TIMUR - Satriyawan, Aziz Nuri (Jurnal Al-Ilmu: Jurnal Penelitian dan Pendidikan Madrasah Ibtidaiyah, 2022)
Human life in the 21st century has undergone many changes and this century also demands quality human resources, especially the world of education. The purpose of this study was to determine the Implementation and Effectiveness of Learning Media in Kedongharjo Village, Mantingan District, Ngawi Regency, East Java. The study used a descriptive qualitative approach. The research subjects were educators, students, and parents. The data collection technique is by using the observation method, interview method and documentation method. The results of the research show that, first, in the early stages of learning, educators attach pictures/photos in front of the class to be precise on the blackboard as a learning medium, then the educator delivers the material to students by intregrating the image media that has been provided, then the teacher asks quations ti the students about learning materials, to find out whether students understand the material well or not second, in order to create a pleasant learning atmosphere, image media is very affective to use in supporting the learning process, because its use is practical and inexpansive and able to foster the enthusiasm of students in the learning process in the 21st century.